Legal Model for Fulfilling Educational Rights for Persons with Disabilities in the Covid-19 Pandemic Era - Abdussamad, Zamroni; Hidayat Muhtar, Mohammad; Alhasni Bakung, Dolot (KnE Social Sciences, 2022)
The state has provided guarantees in the education of all citizens. In addition, the 1945 Constitution has clearly stated that education is a human right. Of course, this includes people with disabilities as the nation’s successors. The fulfillment of the rights of persons with disabilities in Indonesia has various problems in terms of the education pattern, which is still segregated due to lack of accessibility and supporting facilities to fulfill the educational rights of persons with disabilities. This is even more difficult with the policy of learning from home by using online learning facilities. As previously mentioned, the Covid-19 pandemic has forced all students, including persons with disabilities, to adapt to conditions by undergoing distance learning. Of course, various related policies and the distance learning processes must protect people with disabilities to continue receiving education, especially basic education, which must be followed by all Indonesian citizens. Article 4 paragraph (1) of the National Education System Law, which upholds human rights, religious values, cultural values, and national pluralism, implicitly affirms this principle. Therefore, it is necessary to build a mechanism and legal model to fulfill the educational rights of people with disabilities in the era of the Covid-19 pandemic. As for the formulation of the problem in this study, namely: How to ensure disabled people’s right to education? What is the legal model for fulfilling the educational rights of Covid-19 Disabilities? Keywords: persons with disabilities, education rights, Covid-19